(untitled) (Research, Society and Development, 2021)
Independent musical groups are those that act autonomously, without major investments or partnerships, and coordinating their own actions. In this sense, the members of these groups need to develop skills and practice functions that go beyond the musical universe, in order to maintain a good performance and reach their goals. The present study aimed to evaluate the collaborative management of independent musical groups. For this purpose, the Multicriteria Decision Support (MCDA) methodology was used, a field research was carried out, in which representatives of forty-two musical groups from Brasília answered a questionnaire, evaluating the management of their respective groups, according to the criteria established in the evaluation model. The construction of the evaluation model consisted of seven steps: Definition of the problem label, identification of the actors involved in the evaluation process, determination of evaluation elements (criteria), definition of descriptors, construction of value functions, determination of replacement rates and construction of the value tree. Data were processed by Hiview3 software and analyzed based on the developed evaluation model. The ratings obtained in the survey were low, indicating the dissatisfaction of representatives of independent musical groups in Brasília with the collaborative management exercised in their respective groups and demonstrating the need to implement improvements in their management and production systems.